The Role of Marketing Entrepreneur Ability Values in Building Student Entrepreneurship Performance: The Case of Student Business Incubation Program: The Role of Marketing Entrepreneur Ability Values in Building Student Entrepreneurship Performance: The Case of Student Business Incubation Program - Andi Setiawan; Hartono Hartono; Retno Winarti; Sulistyo Sulistyo; Sumanto Sumanto (International Journal of Education, Vocational and Social Science, 2023)
This study is interested in analyzing marketing entrepreneur ability value in influencing entrepreneurship performance. Our study views that marketing hard skills and marketing soft skills are not enough to be a lever factor for Entrepreneurship Performance. The results of research on 237 samples using structural equation modeling revealed the findings of marketing hard skills and marketing soft skills can maximize their role in entrepreneurship performance if both types of marketing competencies can develop marketing entrepreneur ability value as a valuable resource capital for the company.